The Effectiveness of the Team Teaching Method in Improving Conceptual Understanding and Learning Motivation of Grade VII Junior High School - Julanda Adriana Wakum; C. Asri Budiningsih (South Sulawesi Education Development (SSED), 2025)
This study used a quantitative approach with a quasi-experimental design (non-equivalent control group) to analyze the effect of the team teaching method on students' conceptual understanding and learning motivation at SMP Negeri 4 Sentani. The research sample consisted of two groups, namely the experimental group (27 students) who participated in learning using the team teaching method and the control group (28 students) who participated in conventional learning. Data collection was conducted through a five-point Likert scale questionnaire, student engagement observation sheets, and assignment scores as supporting data. The instruments were tested for content and construct validity as well as reliability using Cronbach's Alpha, with all values meeting the standard of >0.70, so the instruments were declared valid and reliable. Data analysis using SmartPLS included factor loading, AVE, cross loading, correlation, composite reliability (rho_c), and R-squared. The results of the study indicate that the team teaching method has a significant effect on students' conceptual understanding and learning motivation. The factor loading values of the team teaching method indicators are very high (0.941–0.959), while the conceptual understanding and learning effectiveness indicators also show high values (0.865–0.979), indicating the success of this method in increasing student engagement and understanding. The AVE value above 0.5 and composite reliability >0.9 indicate that the instrument used is valid and consistent. Correlation analysis shows a strong relationship between the team teaching variable and conceptual understanding (0.991), learning effectiveness (0.989), and learning motivation (0.984). These results confirm that the application of team teaching not only improves material comprehension but also significantly encourages student learning motivation. In conclusion, the team teaching method is effective in improving students' conceptual understanding and learning motivation at SMP Negeri 4 Sentani. This study recommends the routine application of collaborative methods and the exploration of other external factors that can further improve student learning motivation.